Perwujudan Fungsi Hukum Dalam Penyelesaian Sengketa: Relasi Fungsional Konsep Living Law dan Alternatif Penyelesaian Sengketa Pada Konstruksi Hukum Nasional - La Ode Muhammad Taufiq Afoeli (CV. Ulil Albab Corp, 2023)
The existence of law is associated as an entity that functions to realize benefits, justice and certainty. Among the descriptions of these benefits is the efficiency of the law as an instrument of reducing as well as resolving conflicts or disputes in the relations of people's lives. These settlement variants are commonly formatted into two methodical types including litigation or a dispute resolution model that prioritizes agency instruments and/or court decisions as well as non-litigation methods which tend to direct the parties to end disputes through a process of deliberation to reach a consensus outside the court. The non-litigation model has the potential for connection with the concept of living law, which means being more open to using local wisdom as a reference for conflict resolution. By using “traditional law”, the parties involved in the conflict will be more obedient to the substance of the agreement and the parties can independently choose options to end the dispute. This condition can actually be optimized so that the paradigm of dispute resolution is not always dominated by the judiciary and at the same time does not give up legal identity that grows, develops and surrounds national identity.